Analisis Pengaruh Model Pembelajaran Kolaboratif Berbasis Masalah Terhadap Hasil Belajar Peserta Didik Sekolah Dasar - Yossi Nadila; Nur Azmi Alwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The problem-based collaborative learning model can motivate learners to engage in action, emphasize the authenticity of collaborative learning environments, and actively involve students in the learning process with a focus on independent thinking and problem-solving skills. Although numerous experimental studies have been conducted to evaluate the impact of this model on learning outcomes, there has yet to be a comprehensive review that examines and reassesses these findings to strengthen the existing evidence. Therefore, this study aims to analyze the effectiveness of the problem-based collaborative learning model on learning outcomes at the elementary school level. The results of the analysis indicate that this model has a significant impact, with variations in the level of influence ranging from 20% to 81%. From these findings, it can be concluded that the problem-based collaborative learning model can make a significant contribution to enhancing motivation, participation, communication, and student cooperation in the learning process.